Genetic Aspects of Juvenile Rheumatoid Arthritis - Mallaev Sh.Sh; Bobomuratov T.A; Fayziev N.N.; Sultanova N.S.; Dinmuxammadieva D.R. (Genius Journals, 2022)
The article describes the clinical and genetic features of juvenile rheumatoid arthritis and the consequences of the disease after treatment with chronotherapy. The clinical features of the disease, the results of laboratory analysis are important when choosing an effective treatment method. An effective treatment method is characterized by a faster onset of remission, an extension of its duration and a decrease in the side effects of drug treatment
Keywords: juvenile; rheumatoid; prognosis; chronotherapy